De novo transcriptome assembly of Aureobasidium melanogenum CGMCC18996 to analyze the β-poly(L-malic acid) biosynthesis pathway under the CaCO3 addition - Genan Wang; Haisong Yin; Tingbin Zhao; Donglin Yang; Shiru Jia; Changsheng Qiao (Food Science and Human Wellness)
β-Poly(L-malic acid) (PMLA) is a water-soluble biopolymer used in food, medicine and other industries. To date, the biosynthesis pathway of PMLA has not been fully elucidated. In this study, we sequenced the transcriptome of strain Aureobasidium melanogenum under 20 g/L CaCO3 addition. The resulting sequencing reads were assembled and annotated for the differentially expressed genes (DEGs) analysis and novel transcripts identification. The result indicated that with the CaCO3 addition, the tricarboxylic cycle (TCA) cycle and glyoxylate pathway were up-regulated, and it also found that a non-ribosomal peptide synthetase (NRPS) like protein was highly expressed. The DEGs analysis showed a high expression level of malate dehydrogenase (MDHC) and phosphoenolpyruvate carboxykinase (PCKA) in the CaCO3 group, which indicated a cytosolic malate activity. We speculated that the malate should be transported to or synthesized in the cytoplasm, which was then polymerized to PMLA by the NRPS-like protein, accompanied by the up-regulated TCA cycle providing ATP for the polymerization. Depending on the analysis, we assumed that an NRPS-like protein, the TCA cycle, and the cytosolic malate together are contributing to the PMLA biosynthesis.